2016
DOI: 10.1016/j.vaccine.2016.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Can thermostable vaccines help address cold-chain challenges? Results from stakeholder interviews in six low- and middle-income countries

Abstract: HighlightsInterviews (158) conducted with immunization personnel in 6 countries.Respondents are interested in vaccines with improved heat and freeze stability.Most involved in vaccine purchases would pay a slight premium for those features.Most saw value in controlled temperature chain (CTC) use of vaccines.Many highlighted the need for careful consideration of CTC risks/benefits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
56
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(56 citation statements)
references
References 23 publications
0
56
0
Order By: Relevance
“…Emphasis has long been placed on avoiding high temperatures, but, as this study also showed, recent studies have reported exposure to freezing temperature at many stages during distribution [ 12 , 23 , 24 ]. The World Health Organization guidelines specify that the hepatitis B, diphtheria–tetanus–pertussis, diphtheria–tetanus, and tetanus toxoid vaccine must not be frozen [ 12 ].…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Emphasis has long been placed on avoiding high temperatures, but, as this study also showed, recent studies have reported exposure to freezing temperature at many stages during distribution [ 12 , 23 , 24 ]. The World Health Organization guidelines specify that the hepatitis B, diphtheria–tetanus–pertussis, diphtheria–tetanus, and tetanus toxoid vaccine must not be frozen [ 12 ].…”
Section: Discussionmentioning
confidence: 74%
“…To avoid freezing of vaccines, Kolwaite et al conducted a pilot study to assess the effect of “out-of-the-cold-chain” storage in Lao PDR and discovered improved Hepatitis B dose coverage without an increase in adverse reactions [ 25 ]. Some innovative solutions should be considered in the context of developing countries, such as a computerizing temperature monitoring system, development of thermostable vaccines, development of a compact prefilled vaccination device, or the use of a cold box that can manage temperature control on its own for a long duration [ 10 , 14 , 24 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Use of vaccine vial monitors that measure cumulative heat exposure and development of pre-filled injection devices further facilitate ease and safety of vaccination by community health workers and could also help address cold-chain challenges in remote areas [24]. In 2017, MenAfriVac Ò conjugate meningococcal meningitis A vaccine was the first vaccine prequalified by WHO for use outside the cold chain in controlled temperature chain (CTC); use of CTC for a mass vaccination campaign in Chad would have reduced logistics costs by an estimated 50% [25].…”
Section: Discussionmentioning
confidence: 99%
“…Another potential solution for improved vaccine efficacy under difficult storage conditions could be the development of more thermostable vaccines by the pharmaceutical industry [ 28 , 29 ]. However, this possibility is not yet available, and therefore, until then, compliance with the recommended vaccine storage temperatures throughout the entire cold chain remains key to maximize the efficacy of all vaccines used to prevent infectious diseases.…”
Section: Discussionmentioning
confidence: 99%